Broadening conservation funding. (9th September 2019) - Echols, Alex; Front, Alan; Cummins, James
ABSTRACT: Funding for natural resource conservation has been largely static or declining over the past 30 years. Environmental challenges are increasing in number and intensity, requiring improvements in efficiency of conservation delivery and broadening of the base of financial support to address these challenges. The conservation community would benefit from de‐siloing environmental foci and movement to more of a systems approach to intensify conservation. There are new partnerships and opportunities to increase the base and variety of sources of funding. To protect and possibly enhance funding for conservation, key innovations in finance and establishing additional funding sources are required. © 2019 The Wildlife Society. Abstract : Conservation needs are increasing, yet government funding is static. There has not been a significant innovation in conservation funding in over 30 years and innovation is needed that looks beyond principle reliance on government.